Double MOF gradually activated S bond induced S defect rich MILN-based Co(z)-NiMoS for efficient electrocatalytic overall water splitting. Issue 48 (8th December 2021) - Chen, Honglei; Yu, Zebin; Hou, Yanping; Jiang, Ronghua; Huang, Jun; Tang, Wenjun; Cao, Zhaojun; Yang, Bo; Liu, Chunxiang; Song, Haonan
Abstract : Herein, cactus like nanorods with rich S defects and functional group MILN-based Co(z)-NiMoS are synthesized through a facile method. Abstract : Herein, cactus like nanorods with rich S defects and functional group MILN-based Co(z)-NiMoS are synthesized through a facile method. First, we prepared MIL-88B precursor to give a fairly dispersed frame structure, and then Co n + was doped into disulfides, which are rich in sulfur bonds, and the imidazole group was cleverly connected into graphitized carbon via self-etching of ZIF-67. The doping of Co n + and functional groups makes tiny changes in the sulfide lattice, which promotes the unsaturation degree of the S bond and activates it gradually. The prepared semi frame sulfide with a unique structure, on the one hand, ensures the hydrophilicity and multiple active specific surface area, which lays superior functions in morphology. On the other hand, coupling metals that have strong valence change ability and functional groups by active S bonds play an important role in the process of electrocatalytic reaction. Amazingly, disintegration and self-reconstruction of MILN-based Co(z)-NiMoS occurs during oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) due to the activation of the S bond, which provides a new perspective for the overall water splitting mechanism. The electrochemical results show that the MILN-based Co(z)-NiMoS electrocatalyst exhibits overpotentials of HER, OER, and overall water splitting (OWS) to be 169 mV, 170 mV, and 1.466 V, respectively, making it a promising electrode material for OWS applications.